Helicity-driven chiral self-sorting supramolecular polymerization with Ag+: right- and left-helical aggregates. Issue 11 (16th February 2022) - Ok, Mirae; Kim, Ka Young; Choi, Heekyoung; Kim, Seonghan; Lee, Shim Sung; Cho, Jaeheung; Jung, Sung Ho; Jung, Jong Hwa
Abstract : Chiral self-sorting supramolecular polymerization of bola-type terpyridine-based ligands ( R -L 1 and S -L 1 ) comprising R - or S -alanine analogs occurred upon addition of Ag + in one enantiomeric component. Abstract : The study of chiral self-sorting is extremely important for understanding biological systems and for developing applications for the biomedical field. In this study, we attempted unprecedented chiral self-sorting supramolecular polymerization accompanying helical inversion with Ag + in one enantiomeric component. Bola-type terpyridine-based ligands ( R -L 1 and S -L 1 ) comprising R - or S -alanine analogs were synthesized. First, R -L 1 dissolved in DMSO/H2 O (1 : 1, v/v) forms right-handed helical fibers (aggregate I) via supramolecular polymerization. However, after the addition of AgNO3 (0.2–1.1 equiv.) to the R -L 1 ligand, in particular, it was found that aggregate II with left-handed helicity is generated from the [ R -L 1 (AgNO3 )2 ] complex through the [ R -L 1 Ag] + complex via the dissociation of aggregate I by a multistep with an off pathway, thus demonstrating interesting self-sorting properties driven by helicity and shape discrimination. In addition, the [ R -L 1 (AgNO3 )2 ] complex, which acted as a building block to generate aggregate III with a spherical structure, existed as a metastable product during the formation of aggregate II in the presence of 1.2–1.5 equiv. of AgNO3 . Furthermore, the AFM and CD results of two samples prepared using aggregates I and III with different volume ratios were similar to those obtained upon the addition of AgNO3 to free R -L 1 . These findings suggest that homochiral self-sorting in a mixture system occurred by the generation of aggregate II composed of the [ R -L 1 Ag] + complex via the rearrangement of both, aggregates I and III. This is a unique example of helicity- and shape-driven chiral self-sorting supramolecular polymerization induced by Ag + starting from one enantiomeric component. This research will improve understanding of homochirality in complex biological models and contribute to the development of new chiral materials and catalysts for asymmetric synthesis.